A Novel Data Mining Algorithm for Mathematics Teaching Evaluation - Gang Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
AbstractWith relative theory about technology of datamining and recommender model of user’s interest, this paper presents the methodof MWFP-TREE based on the combination between recommender model idea of user’sweight and the minimum weighted FP-TREE method. Compared to traditional method,this method does not only carry out dimension reduction of raw data to improvethe efficiency of a constructing tree but it also performs association rulemining and improves mining effect. This method is applied to mathematics  teaching evaluation in one university and it findsout different evaluations from different students respectively consideringstudents’ information and teachers’ information while it is not similar totraditional thought which is only to perform mining direction based onteachers’ information. Towards mining regulations and results, it providessignificant referential values for objectivity of teaching evaluation andteaching directions. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4809